Three-dimensional lithospheric-scale thermal model as supporting tool for new exploration campaigns for geothermal resources: Insights from the Calabria region (Southern Italy) - G. Vespasiano; G. Floridia; M. Giuffrida; M. Viccaro; A. Bloise; R. De Rosa; M. Cacace; I. Fuoco; M.F. La Russa; F. Muto; R. Dominici; L. Russo; et al. (Geothermics, 2026)

Impact and evaluation of potential implications of coastal plains on soil greenhouse gas emissions: Insights from the Sibari Coastal Plain (Calabria, Southern Italy) - C. Apollaro; G. Vespasiano; I. Fuoco; M. Taussi; R. De Rosa; M.F. La Russa; A. Guido; D. Di Curzio; A. Renzulli; L. Russo; F. Ciniglia; F. D'Amico; et al. (Science of The Total Environment, 2025)

Assessing potentially toxic elements (PTEs) content in asbestos and related groundwater: A review of the levels detected - A. Bloise; I. Fuoco; G. Vespasiano; F. Parisi; M.F. La Russa; C. Piersante; G. Perri; S. Filicetti; A. Pacella; R. De Rosa; C. Apollaro (Science of The Total Environment, 2024)

Quantitative Assessment of Geosites and Mine Heritage as a Resource: The Case Study of Lungro Salt Mine (Calabria, Italy) - M. F. La Russa; A. Patanè; C. Apollaro; A. Bloise; I. Fuoco; M. Ricca; L. Russo; G. Vespasiano (Geoheritage, 2024)
In this work, the old Lungro mining site was studied by applying two classification methods (Brilha and IELIG Method), considering the site-specific scientific, educational, touristic, and degradation aspects, to promote it as a geosite. The results were compared with those from other worldwide areas, and a potential re-evaluation in the tourism sector was suggested, considering historical data and geological issues. The methods used evaluate the Lungro site an average score from a scientific perspective, and from high to very high for the tourist-educational aspects. On the contrary, lower scores were found regarding the degradation of the site due to natural phenomena, led to a lower total score. The obtained results are comparable with other similar restored mining areas, located in various parts of the world which today represent important geotourists sites recognized internationally. Based on these results, the safest, most cost-effective, and straightforward way to preserve and restore the site is by creating a “Geotourism Route.“ . This choice would increase awareness of the area, providing the general public, including the curious and “non-experts”, with an understanding of various geological processes and the extensive history of the mine. A campaign to promote and preserve the Lungro site as a geoheritage will be encouraged, with significant implications for tourism at the local, national, and international levels.